Modeling Industrial Growth and Agglomeration Economies in the Manufacturing Sector of Pakistan (The Pakistan Development Review, 1989)
The uneven distribution of production and consumption is one of the several problems being faced by the less developed countries (LDCs). The governments of these countries are pursuing multidimentional policies to develop the backward areas and to put a check on overcrowded cities. For example, in Pakistan National Development Finance Corporation (NDFC) has been established to promote industries in backward areas. Moreover, tax holidays, import facilities and loans on easy terms are some of the devices which are being used to promote the backward regions. Besides, Lahore and Karachi are facing serious economic problems due to rapid urbanization. Their population is growing 1 percent to 2 percent above the national growth rate of population.1 On the other hand, several geographicallocations are still backward, despite policy measures taken by the public sector. 2 It is important that, if these policies fail to improve the situation, a better rationale should be explored in this respect. The purpose of this study is to identify the sources of industrial concentration in Pakistan. Besides, we will be looking at reasons for the concentration of industries at certain locations. One way to explain this phenomena is through agglomeration economies. We will develop a model to study this event. If our model can explain the increasing returns to scale, which is a way to measure agglomeration economies,3 then, we may be able to utilize this knowledge to provide a base for policy formulation to develop the backward areas, as well as, for efficient use of public finance.